Conférence: «Histoire de l'art et féminisme - Rencontre entre deux champs» - Institut de recherches et d'études féministes; Réseau Québécois en études féministes (2018)
Avec Thérèse St-Gelais, directrice de l'Institut de recherches et d'études féministes et professeure au Département d'histoire de l'art.
Keywords: amériques; approches et analyses; arts; corps; création; discipline; femmes* artistes; histoire de l'art; histoire des femmes*; histoire du féminisme; oeuvre; performance; point de vue situé; postmodernisme; québec; ressource en ligne; régions géographiques; thématiques; violences; émotions

"Why Should Our Bodies End at the Skin?": Embodiment, Boundaries, and Somatechnics - SHILDRICK, MARGRIT (Hypatia, 2015)
Donna Haraway's enduring question—"Why should our bodies end at the skin?" (Haraway 1990, 220)—is ever more relevant in the postmodern era, where issues of bodies, boundaries, and technologies increasingly challenge not only the normative performance of the human subject, but also the very understanding of what counts as human. Critical Disability Studies has taken up the problematic of technology, particularly in relation to the deployment of prostheses by people with disabilities. Yet rehabilitation to normative practice or appearance is no longer the point; instead, the lived experience of disability generates its own specific possibilities that both limit and extend the performativity of the embodied self. I look at what is at stake in the challenge to the Western logos that comes specifically from the capacities of the disabled body, understood not as a less than perfect form of the normative, but as figuring difference in a nonbinary sense. Feminist theory has long contested the isomorphism of the logos, but I go beyond simply setting out the grounds for revaluing multiple variant forms. The feminist turn to Jacques Derrida and Gilles Deleuze opens up the problematic to a celebratory positioning of difference and transcorporeality as the very conditions of life.
Keywords: EDI; approches et analyses; arts; bioéthique; corps; cours; discipline; philosophie; postmodernisme; premier cycle; prothèses; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; technologie; thématiques; études critiques du handicap; études littéraires

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists -- including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan -- whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

The Anti-aesthetic: essays on postmodern culture - Foster, Hal (Bay Press, 1983)
For the past thirty years, Hal Foster has pushed the boundaries of cultural criticism, establishing a vantage point from which the seemingly disparate agendas of artists, patrons, and critics have a telling coherence. In The Anti-Aesthetic, preeminent critics such as Jean Baudrillard, Rosalind Krauss, Fredric Jameson, and Edward Said consider the full range of postmodern cultural production, from the writing of John Cage, to Cindy Sherman's film stills, to Barbara Kruger's collages. With a redesigned cover and a new afterword that situates the book in relation to contemporary criticism, The Anti-Aesthetic provides a strong introduction for newcomers and a point of reference for those already engaged in discussions of postmodern art, culture, and criticism. Includes a new afterword by Hal Foster and 12 black and white photographs.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; approches et analyses; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; postmodernisme; premier cycle; périodes historiques; thématiques